Meteorological forecast data: Coupling NWP and CFD Modeling. Merging the datasets: Deliverable D2.2 - Couto, António (2022)
Project OPTIGRID - Methodology for Analysis of Dynamic Line Capacity and Optimized Management of Electric Grids: https://optigrid.lneg.pt/